KONTRIBUSI DUKUNGAN ORANG TUA TERHADAP KESEHATAN MENTAL SISWA SMA - Anastika, Farida; Soeharto, Soeharto (Consilium: Jurnal Program Studi Bimbingan dan Konseling, 2014)
This research is descriptive quantitative. The sample is the eleventh grader in total of 155 students. The data are collected through questionnaire. Data analysis for the first and second hypotheses are done through One Tail Test t-test with the left party; while for the third hypothesis, the regression analysis using SPSS is utilized. The results show that: (1) the level of student mental health was considered high, (2) the level of parental support to the students is considered high, (3) the contribution of parental support to the student mental health is up to 25.5 %.